2014
DOI: 10.1016/j.rmed.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning sprays, household help and asthma among elderly women

Abstract: Weekly household use of cleaning sprays may have a deleterious effect on asthma. It is important to take into account household help to limit misclassification bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 43 publications
7
46
1
1
Order By: Relevance
“…Our results suggested an inflammatory role of cleaning agents in spray form and are consistent with previous results reported among elderly females from the E3N survey [5] and among Spanish professional cleaners [9]. In E3N, a significant association between the weekly use of sprays at home and current asthma was reported only among females without anti-inflammatory therapy (inhaled corticosteroids) [5].…”
Section: Agora Correspondence |supporting
confidence: 91%
See 3 more Smart Citations
“…Our results suggested an inflammatory role of cleaning agents in spray form and are consistent with previous results reported among elderly females from the E3N survey [5] and among Spanish professional cleaners [9]. In E3N, a significant association between the weekly use of sprays at home and current asthma was reported only among females without anti-inflammatory therapy (inhaled corticosteroids) [5].…”
Section: Agora Correspondence |supporting
confidence: 91%
“…Our findings add to the evidence that household exposures to cleaning products, especially in spray form, may represent an important emerging life course public health issue [2,5]. Our results support the recent recommendations to investigate preventive measures for consumers [10], and to limit both the production and use of household cleaning products in spray form.…”
Section: Agora Correspondence |supporting
confidence: 86%
See 2 more Smart Citations
“…However, the exact category of cleaning products and their chemicals causing adverse health effects as well as the route of exposure still need to be clarified. Some studies point to products in spray-form to be associated with risk of inhalation and reported health effects (Bédard et al, 2014;Le Moual et al, 2014;Vernez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%